The Role of Calcium and Glucose on the Increasing of Parasitemia Value and Hemolysis into Plasmodium falciparum-infected Erythrocyte - Verry Asfirizal (Chemical Engineering Diponegoro University, 2016)
Erythrocyte infected by Plasmodium experiences various changes of shape and function. The permeability increases upon various dissolved material including amino acid, glucose, vitamin, nucleotide, purine, anion/cation and organic/inorganic and also others simple dissolved materials such as sorbitol, choline and chloride-ion. The increasing of permeability is very needed by Plasmodium to provide nutrients for internal growth. The objectives of this research were to determine the increasing of parasitemia value and hemolysis on erythrocyte infected by Plasmodium falciparum. The medium culture used for growing Plasmodium falciparum was RPMI 1640 that produced parasitemia 15%, inoculation was conducted to produce sub-culture that produced parasitemia 20% and divided into calcium, glucose and control (CM 10%) treatment with 3 times replications. Observation was conducted from the first day to sixth day after treatment. Parasitemia and hemolysis parameters as growth indicators were observed. Difference among treatments groups were analyzed using ANOVA and followed by Duncan Multiple Range Test (DMRT α=0.05). The result showed that the application of calcium + glucose produced the highest number of parasitemia (11.87±4.71) (means ±SD) and hemolysis (0.278+0.012) compared with others applications i.e. calcium, glucose and control medium culture (10% CM). This application produced significant difference (p<0.05). It was concluded that calcium and glucose had important to increase parasitemia and hemolysis of Plasmodium falciparum-infected erythrocyte